Design and fabrication of the testing model of the vehicle structure test system - Abdullah, Kassim Abdulrahman; Cheah , Siew Loong (IIUM Press, 2011)
This chapter describes the procedures followed in developing the test model of vehicle structure testing and also explores a technique whereby durability aspects of the vehicle structure can be assessed by simple structural surface (SSS) method and finite element analysis (FEA) that can be carried out at an early design stage of vehicle structure